METHODOLOGICAL PROBLEM OF IMAGE CATEGORY IN SUBJECT-OBJECT INTERACTION - A.A. Strelenko; M.N. Kiseleva (Juvenis Scientia, 2019)
The article is devoted to the methodological problem of the category of image in subject-object interaction. The role of adequate reflection of the image of a person in the process of interpersonal interaction is determined. The problem of image in foreign, Russian and Belarusian psychology is considered. The theoretical approaches to the study of the image problem are analyzed. Differences in the general psychological and socio-psychological approaches in the study of socio-perceptual processes, including socio-perceptual images, are noted. The stages of the empirical level of studies of the image of a person are given. A synthesized approach is considered in detail, in which data on the hierarchical structure and content of human images are presented. The advantages of the SOCH(I) technique are considered - the structure of a person’s image (hierarchical) and the features of its use in scientific psychological research and psychological practice. Empirical studies using the SOCH(I) technique are indicated.